Mechanisms of inflammation after ischemic stroke in brain-peripheral crosstalk - Xie, Ling; He, Ming; Ying, Caidi; Chu, Haifeng (Frontiers in Molecular Neuroscience, 2024)
Stroke is a devastating disease with high morbidity, disability, and mortality, among which ischemic stroke is more common. However, there is still a lack of effective methods to improve the prognosis and reduce the incidence of its complications. At present, there is evidence that peripheral organs are involved in the inflammatory response after stroke. Moreover, the interaction between central and peripheral inflammation includes the activation of resident and peripheral immune cells, as well as the activation of inflammation-related signaling pathways, which all play an important role in the pathophysiology of stroke. In this review, we discuss the mechanisms of inflammatory response after ischemic stroke, as well as the interactions through circulatory pathways between peripheral organs (such as the gut, heart, lung and spleen) and the brain to mediate and regulate inflammation after ischemic stroke. We also propose the potential role of meningeal lymphatic vessels (MLVs)-cervical lymph nodes (CLNs) as a brain-peripheral crosstalk lymphatic pathway in ischemic stroke. In addition, we also summarize the mechanisms of anti-inflammatory drugs in the treatment of ischemic stroke.